Real‐world clinical outcomes of sofosbuvir and velpatasvir treatment in HCV genotype 1‐ and 2‐infected patients with decompensated cirrhosis: A nationwide multicenter study by the Japanese Red Cross Liver Study Group. Issue 11 (3rd July 2021) - Tada, Toshifumi; Kurosaki, Masayuki; Nakamura, Shinichiro; Hasebe, Chitomi; Kojima, Yuji; Furuta, Koichiro; Kobashi, Haruhiko; Kimura, Hiroyuki; Ogawa, Chikara; Yagisawa, Hitoshi; Uchida, Yasushi; Joko, Kouji; et al.
Abstract: The real‐world virological efficacy and safety of interferon‐free direct‐acting antiviral (DAA) therapy with sofosbuvir (SOF) and velpatasvir (VEL) were assessed in hepatitis C virus (HCV) genotype 1‐ and 2‐infected patients with decompensated cirrhosis. A total of 65 patients with HCV‐related decompensated cirrhosis (Child‐Pugh score of 7 points or more) who were treated with the SOF/VEL regimen were enrolled. The sustained virological response (SVR) rate and safety profile were analyzed. SVR was defined as undetectable serum HCV RNA at 12 weeks after the end of treatment (SVR12). The percentages of patients with undetectable HCV RNA at 4, 8, and 12 weeks after the start of therapy were 81.2% (95% confidence interval [CI], 69.5–89.9) (52/64), 98.4% (95% CI, 91.2–100.0) (60/61), and 98.5% (95% CI, 91.7–100.0) (64/65), respectively. The overall SVR rate was 92.3% (95% CI, 83.0–97.5) (60/65). Albumin–bilirubin (ALBI) scores decreased during and after treatment ( p < 0.001), and there were significant differences between baseline and end of treatment and between baseline and SVR12. Subgroup analyses showed no significant differences in SVR rates according to patient age, sex, HCV genotype (subtype), Child‐Pugh classification, modified ALBI grade, presence of ascites, presence of hepatic coma, or history of hepatocellular carcinoma. In all subpopulations, the SVR rates were higher than 80%. There were no severe adverse events associated with the treatment. The SOF/VEL regimen showed good virological efficacy and acceptable safety even in patients with HCV‐related decompensated cirrhosis. Highlights: The efficacy and safety of sofosbuvir and velpatasvir were assessed in hepatitis C virus patients with decompensated cirrhosis. The overall sustained virological response rate was 92.3% and albumin–bilirubin scores decreased during and after treatment (p <0.001). There were no severe adverse events associated with the treatment.